A study to determine patients perception of utilization of health care services at siavonga district hospital - Inambao, Loveness Nkole (Lusaka: University of Zambia , School of Medicine, 2009)
The study sought to determine patients' perception of hospitalization and utilization of health care services at siavonga district hospital. Litearture review revealled that there has been no such study on this topic conducted before in Zambia.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Hospitalization; Patients; Hospital patients --Zambia --Attitudes.